Marx : the alternative to capitalism - Allen, Kieran, 1954- (London : Pluto Press, 2017)
An accessible and comprehensive overview of the ideas of Karl Marx that elucidates his theories and suggests crucial alternatives to capitalism.
Cover; Contents; Preface; Acknowledgements; Introduction; 1. Rebel with a Cause; 2. A for Profit Society; 3. Alienation; 4. Social Class; 5. Gender and Race; 6. How We Are Kept in Line; 7. Historical Materialism; 8. Crash: How the System Implodes; 9. Utopia or Revolution; 10. After the Revolution; 11. The Economics of Socialism; 12. Into the Beyond; Notes; Guide to Further Reading; Select Bibliography; Index
Includes bibliographical references (pages 224-228) and index.
Originally published in 2011 with title: Marx and the alternative to capitalism.
Print version record.
eBooks on EBSCOhost
Keywords: Marx, Karl, -- 1818-1883 -- Political and social views; Marx, Karl, -- 1818-1883; Communism; Socialism; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; Communism; Political and social views; Socialism; Electronic book